Correlation between severity of pulmonary embolism and obstructive sleep apnea using computed tomography pulmonary artery obstruction index and right ventricular to left ventricular diameter ratio as severity indices - Marwa Makboul; Doaa M. Magdy; Ahmed Metwally; Shimaa Farghaly (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background Recent studies have shown a bidirectional association between pulmonary embolism (PE) and obstructive sleep apnea (OSA), and due to their morbidity and mortality, this contributes significantly to the global health-care burden, so this study aims to assess the relationship between PE and OSA severity using the obstruction index of the pulmonary artery and the ratio of right ventricular to left ventricular (RV/LV) diameter as severity indices. Results The study comprised 138 patients with a high clinical suspicion of PE that was verified by computed tomography pulmonary angiography. In addition to calculating the RV/LV diameter ratio and pulmonary artery obstruction index (PAOI), the pulmonary embolism severity index was also calculated, and the Epworth Sleepiness Scale and polysomnography (PSG) were used to assess all patients for OSA. Finally, three groups of patients (< 15% vs. 15–50% vs. > 50%) were created based on the PAOI. Age, gender, neck, and waist circumference showed no significant difference between the three groups, but there were significant correlations between higher PAOI and increased BMI, provoked PE, increased rate of thrombolysis, increase in the recurrence of venous thrombosis, a longer length of hospital stay, and a higher ratio of RV/LV diameter (p value was < 0.05). Regarding PSG, a significant positive correlation was observed between the apnea–hypopnea index (AHI) and higher PAOI as well as the ratio of RV/LV diameter (r = 0.957, p value < 0.001) and (r = 0.825, p value < 0.001), respectively, with the obstruction index of the pulmonary artery > 40%, and the ratio of RV/LV diameter > 1 being found to be predictors of severe sleep apnea. Conclusions We deduced from this study that there is a substantial relationship between the severity of PE and the severity of OSA, as patients with higher obstruction of the pulmonary artery had severe OSA, and both the obstruction index of the pulmonary artery > 40% and the ratio of RV/LV diameter > 1 were considered significant predictors for the severity of OSA among the acute PE patients.